A novel link allocation method for vehicle‐to‐vehicle‐based relaying networks. Issue 1 (20th January 2014) - Zheng, Qiang; Zheng, Kan; Chatzimisios, Periklis; Long, Hang; Liu, Fei
Abstract: Vehicle‐to‐infrastructure (V2I) and vehicle‐to‐vehicle (V2V) are two main communication modes in vehicular ad‐hoc networks. V2V is one of the key techniques to enhance the coverage and capacity of the V2I communication system. In this paper, we propose a novel link allocation method involving both V2I and V2V communications to enhance the throughput of the V2V‐based relaying network. Jointing the links scheduling and radio resource allocation to V2V links is an Non‐deterministic Polynomial (NP) hard problem with huge complexity. The proposed scheduling scheme adopts a dynamic optimization algorithm based on the multi‐choice knapsack problem to solve the problem with acceptable complexity. Simulation results demonstrate that the proposed scheme significantly improves throughput of vehicular networks and achieves higher fairness. Copyright © 2014 John Wiley & Sons, Ltd. Abstract : A novel link allocation method is proposed involving both vehicle‐to‐infrastructure (V2I) and vehicle‐to‐vehicle (V2V) communications to enhance the throughput of the V2V‐based relaying network. The proposed scheme joints the links scheduling and radio resource allocation to V2V links with acceptable complexity.